Karakteristik komposit sandwich dengan inti (core) open cell foam bambu berlubang - P.D. Setyawan; S. Sugiman; S. Sinarep; H. Hilwan (Dinamika Teknik Mesin, 2023)
The sandwich composite employed in this study is made of bamboo open-cell foam with plywood skin. The fibre volume percentage in the bamboo foam core was 15%, and PVAc glue was used. The open-cell foam core has a square-shaped hollow in the centre with spacings of 30mm, 40mm, and 60mm. The goal of this study is to describe sandwich composites made using hollow bamboo open-cell foam cores. Density testing (ASTM C271), flatwise compression testing (ASTM C365-05), flexural testing (ASTM C393), and water absorption testing (ASTM C272) were among the tests performed. Sandwich composites with core-opened cell foam with holes had lower average density, specific flatwise compressive strength, and specific bending strength than sandwich composites without holes, according to the study's findings. The average density of the sandwich composite with core-opened cell foam with holes dropped by 6-13% as compared to the sandwich composite without holes. The average-specific flatwise compressive strength of the sandwich composite with a hollow core decreased by 2-20%. The sandwich composite's average specific bending strength was reduced by 40-50% when the core-opened cell foam with holes was used. The percentage of water absorption in the sandwich composite is the inverse. With this feature, it is believed that hollow bamboo open-cell foam would become more widely used.